Cloud computing as a tool for improving business competitiveness - Michał Wišniewski (Foundations of Management, 2013)
This article organizes knowledge on cloud computing presenting the classification of deployment models, characteristics and service models. The author, looking at the problem from the entrepreneur's perspective, draws attention to the differences in the benefits depending on the cloud computing deployment models and considers an effective way of selection of cloud computing services according to the specificity of organization. Within this work, a thesis statement was considered that in economic terms the cloud computing is not always the best solution for your organization. This raises the question, "What kind of tools should be used to estimate the usefulness of the model cloud computing services in the enterprise?"
Keywords: 650; cloud computing; data processing; opportunities; threats; service models; deployment models; the characteristics of cloud computing; innovation; estimating operating costs